C-peptide is a predictor of telomere shortening: A five-year longitudinal study - Ghoussaini, Racha; Tamim, Hani; Elbejjani, Martine; Makki, Maha; Nasreddine, Lara; Ismaeel, Hussain; Nasrallah, Mona P.; Zgheib, Nathalie K. (Frontiers in Endocrinology, 2022)
Aim Relative telomere length (RTL) predicts the development of many age-related diseases. Yet, few studies have evaluated their longitudinal effect on RTL. We investigated longitudinally the association between cardiometabolic risk factors and RTL. Methods This was a longitudinal study with a 5-year follow-up period, based on data collected in 2014 and 2019. Of 478 participants in 2014, 198 consented to be followed-up in 2019. The associations between RTL and risk factors were analyzed using t-test, ANOVA or simple linear regression as applicable. Results RTL was significantly shortened after 5 years (P<0.001). Older age (P=0.018) and gender (P=0.05) were significantly associated with shorter RTL at follow-up. Higher baseline C-peptide correlated with shorter RTL (P=0.04) and shortening of RTL (P=0.03) after 5 years. Multivariate linear regression including both age and gender revealed a significant trend for C-peptide and change in RTL after 5 years (P=0.04). Interestingly, there was a trend of shorter RTL at follow-up with diabetes, though the findings were not statistically significant. Conclusions Higher C-peptide level contributes to telomere shortening over time, suggesting that metabolic dysregulation may play a role in early aging. Further understanding of this relationship and addressing high C-peptide levels can be important to prevent premature aging.